The kingdom of God: a biblical theology - Perrin, Nicholas (Biblical Theology for Life Ser., 2019)
The Kingdom of God by Nicholas Perrin explores the contours of the kingdom by answer the important 'what,' 'who,' and 'how' questions. This comprehensive study brings together careful exegesis of the Old and New Testaments with thoughtful attention to how the kingdom-ethic applies to God's subjects today.